THE EFFECT OF THE GENERATIVE LEARNING MODEL ASSISTED BY STUDENT WORKSHEETS ON EIGHTH-GRADE STUDENTS' SCIENCE LEARNING OUTCOMES - Tata Yohana; Yurnetti Yurnetti; Tuti Lestari; Monica Prima Sari (Universe, 2026)
Students' science learning outcomes are influenced by the instructional strategies and learning resources used during the learning process. The Generative Learning model, supported by Student Worksheets, is expected to promote active knowledge construction and improve students' understanding of scientific concepts. This study aimed to examine the effect of the Generative Learning model assisted by Student Worksheets on eighth-grade students' science learning outcomes. A quasi-experimental research design employing a posttest-only control group design was used. The participants were selected through purposive sampling, with one class assigned as the experimental group receiving instruction using the Generative Learning model assisted by Student Worksheets and another class serving as the control group receiving conventional instruction. Students' science learning outcomes were measured using a validated multiple-choice test. The collected data were analyzed using normality, homogeneity, and independent-samples t-tests. The results showed that the experimental group achieved a higher mean score (89.87) than the control group (86.00). Furthermore, hypothesis testing revealed a statistically significant difference between the two groups (t = 11.37, p < 0.05), indicating that the Generative Learning model assisted by Student Worksheets significantly improved students' science learning outcomes. These findings suggest that integrating the Generative Learning model with Student Worksheets is an effective instructional approach for enhancing science learning among eighth-grade students.